Basic electrical and instrumentation engineering - Sivaraman, Pandarinathan; Sharmeela, C.; Nayagi, A. Thaiyal; Mahendran, R. (Electrical engineer) (Wiley-Scrivener, 2021)
"Electrical and instrumentation engineering is changing at a rapid pace, and books like this give the engineer in the field a valuable reference work to consult. Students are able to use this book as a learning tool, and professors and industrial short courses are able to use it as a textbook."--